Changes in Anthropometric Parameters and Physical Fitness in Older Adults After Participating in a 16-Week Physical Activity Program [Cambios en Los Parámetros Antropométricos y la Condición Física en Adultos Mayores Luego de Participar en Un Programa de Actividad Física de 16 Semanas] - Herrera-Valenzuela, T (Universidad Nacional de Colombia, 2020)
Introduction: Physical activity is important for achieving healthy aging. Objective: To analyze changes in anthropometric parameters and physical fitness among Chilean older adults after participating in a 16-week physical activity program and to evaluate whether there were differences in relation to their baseline nutritional status or not. Materials and methods: Pre-experimental quantitative study. The study population consisted of 176 older adults (155 women and 21 men) distributed in three groups: normal weight (n=56), overweight (n=67) and obese (n=53). The following variables were evaluated: body mass index (BMI), waist circumference (WC), waist-to-height ratio (WHR) and physical fitness. Results: Significant decreases between pre-and post-measurements were found for WC (p<0.001), BMI (p=0.015), and WHR (p<0.001). Improvements were observed in the following tests: chair stand (p<0.001), arm curl (p<0.001), 2-min step (p<0.001), chair sit-&-reach (p=0.018) and back scratch (p=0.014). Regarding BMI, significant changes were observed between normal weight vs. overweight participants (p=0.001) and between normal weight vs. obese participants (p=0.001). Conclusion: Older adult participants that regularly attended the physical activity program were able to reduce their WC, BMI and WHR, and also improved their physical-functional performance on the chair stand, arm curl, 2-min step, chair sit-&-reach and back scratch tests. In addition, anthropo-metric parameters and physical fitness also improved regardless of their baseline nutritional status. © 2020, Universidad Nacional de Colombia. All rights reserved.